Pemberdayaan Masyarakat Nelayan Pulau Karimata dalam Kegiatan Monitoring Terumbu Karang - Kurniadi, Bambang; Minsas, Sukal; Helena, Shifa; Nurdiansyah, syarif Irwan (Lembaga Dongan Dosen, 2023)
Coral reefs are the main ecosystem of marine waters, having an ecological function as a habitat for most marine biota. Apart from that, it also functions as a sea wave defense in the first phase, so it can protect coastal areas including mangroves and settlements from wave abrasion. The fertility of coral reefs is an indicator of the fertility of the waters, and the abundance of potential biota for food such as fish and mollusks and other phyla. The aim of this PKM activity is to provide outreach and assistance to the Karimata coastal fishing community in an effort to monitor the health of coral reefs in the waters with Line Intercept Transect method of Karimata Island. The partners for this activity were the Betok Jaya village community consisting of teenagers and parents including housewives, totaling 25 participants and carried out for 7 days. The results of the activity evaluation show that partners in this activity have a good understanding of the importance of monitoring coral reef growth, and have skills in carrying out coral reef monitoring techniques and reporting accompanied by supporting data.